Race, place, and HIV: The legacies of apartheid and racist policy in South Africa. (March 2022) - Bell, Griffin J.; Ncayiyana, Jabulani; Sholomon, Ari; Goel, Varun; Zuma, Khangelani; Emch, Michael
Abstract: Black South Africans accounted for 6.2 out of 6.4 million people living with HIV in South Africa in 2012, highlighting extreme racial disparities in HIV infection. These racial disparities are the result of structural and historical factors, specifically, the racist policies which were facilitated by segregation before, during, and after Apartheid. First, we describe the theoretical context of how racist policies and segregation are linked to HIV prevalence. Next, using data from a 2012 national survey of South Africans (SABSSM IV) and Statistics South Africa (StatsSA), we describe the race-specific geospatial distribution of HIV in South Africa, provide empirical evidence for the impact of Apartheid on important risk factors for HIV infection, and describe the relationship between these risk factors and HIV within racial groups. Using multilevel logistic regression, we find that segregation increases the odds of HIV infection among Black South Africans, even after adjusting for many covariates which are sometimes blamed, in place of structural factors, for a higher HIV prevalence in Black South Africans. We found that the estimated odds of infection in the most segregated municipality was 1.95 (95% CI: 1.15, 3.32) times the odds of infection in the least segregated municipality for Black South Africans. In addition to segregation, we also find other covariates to be differentially associated with HIV infection depending on race, such as gender, age, and sexual behavior. We also find that the HIV infection odds ratio comparing Black and Coloured (i.e., multiple ethnic groups with mixed ancestries from Africa, Asia, and Europe) South Africans varies over space. These results continue to build evidence for the influence of structural and historical factors on the modern geospatial and demographic distribution of HIV. Highlights: HIV prevalence was 21% in Black South Africans in 2012. HIV prevalence varied across South African municipalities. The geospatial heterogeneity in HIV prevalence remained after stratifying by race. Segregation was positively associated with HIV in Black South Africans. The legacy of Apartheid continues to drive the distribution of HIV infections.